ANALISIS MARKETING CAPABILITY, CUSTOMER ENGAGEMENT, CUSTOMER PERCEPTION DAN PURCHASE INTENTION PRODUK BIHUN JAGUNG “PADAMU”SURABAYA - MARIA WIDYASTUTI; STEVASYA CHANGDA (Catholic University Musi Charitas, 2019)
This research was made to identify the effect of Marketing Capability, Customer Engagement, Customer Perception toward Purchase Intention on Bihun Jagung “Padamu” Products in Surabaya. This research was carried out by distributing questionnaires to 75 respondents who knew the corn vermicelli “Padamu” product. The analysis technique used in this study is quantitative with a non- probability sampling method that is purposive sampling. The results of this study indicate that Marketing Capability, Customer Engagement, Customer Perception have a strong influence toward Purchase intention